A Transit-Oriented Development Concept Model to Reduce Traffic Congestion in Urban Area - Muhammad Andika Satrugna Mahardhika; Erma Suryani; Alifiansyah Arrizqi Hidayat (IPTEK Journal of Proceedings Series, 2020)
Traffic congestion have caused many impacts and losses both in terms of transportation, but also in terms of environmental, economic and social aspects. The increasing number of private vehicles and the decline in public interest in using public transportation is one of the main factors. The decline in public interest in using public transportation is influenced by several reasons, such as ease of access, lack of modes of transportation available, the duration of waiting time, and the duration of travel time. The TOD concept is used because it is a combination of urban planning development and transportation system design, which can help to solve transportation problems especially in urban areas. This study aims to identify and examine how TOD can increase the use of transit modes and transportation efficiency. This study used the System Dynamics model as a means of conceptual modeling (Causal Loop Diagrams) which will describe in detail the factors that will encourage the use of transit modes and improve the efficiency of the transportation system. The results of this study are expected to help provide an overview for policy makers or related parties in determining future directions and strategies related to the existing urban transportation system.